A Potential Peptide From Soy Cheese Produced Using Lactobacillus delbrueckii WS4 for Effective Inhibition of SARS-CoV-2 Main Protease and S1 Glycoprotein - Chourasia, Rounak; Padhi, Srichandan; Chiring Phukon, Loreni; Abedin, Md Minhajul; Singh, Sudhir P.; Rai, Amit Kumar (Frontiers in Molecular Biosciences, 2020)
The COVID-19 pandemic caused by novel SARS-CoV-2 has resulted in an unprecedented loss of lives and economy around the world. In this study, search for potential inhibitors against two of the best characterized SARS-CoV-2 drug targets: S1 glycoprotein receptor-binding domain (RBD) and main protease (3CLPro), was carried out using the soy cheese peptides. A total of 1420 peptides identified from the cheese peptidome produced using Lactobacillus delbrueckii WS4 were screened for antiviral activity by employing the web tools, AVPpred, and meta-iAVP. Molecular docking studies of the selected peptides revealed one potential peptide ‘KFVPKQPNMIL' that demonstrated strong affinity towards significant amino acid residues responsible for the host cell entry (RBD) and multiplication (3CLpro) of SARS-CoV-2. The peptide was also assessed for its ability to interact with the critical residues of S1 RBD and 3CLpro of other β-coronaviruses. High binding affinity was observed towards critical amino acids of both the targeted proteins in SARS-CoV, MERS-CoV, and HCoV-HKU1. Binding energy of KFVPKQPNMIL against RBD and 3CLpro of the four viruses ranged from -8.45 to -26.8 kcal/mol and -15.22 to -22.85 kcal/mol, respectively. The findings conclude that cheese, produced by using Lb. delbrueckii WS4, could be explored as a prophylactic food for SARS-CoV-2 and related viruses. In addition, the multi-target inhibitor peptide, which effectively inhibited both the viral proteins, could further be used as a terminus a quo for the in vitro and in vivo function against SARS-CoV-2.